Allocation of operational decisions in retail supply chains. (15th July 2022) - Kurtuluş, Mümin; Nakkas, Alper; Ülkü, Sezer
Abstract: We consider a supply chain where a single manufacturer sells multiple products via a single retailer who faces uncertain consumer demand for multiple variants in its assortment. First, we consider a model where the retailer is responsible for making assortment and stocking quantity decisions and bears the associated risks. Then, we consider a model where the retailer delegates assortment and stocking quantity decisions and the associated risks to the manufacturer. We investigate how delegation of operational decisions and associated costs impacts operational decisions and profitability of each member in the channel. Our findings suggest that delegation of operational decisions can lead to a win-win outcome for the retailer and manufacturer because delegation of operational decisions can serve as a tool to mitigate inefficiencies due to double marginalization in the channel.